Pengembangan Alat Evaluasi Pembelajaran Berbasis Gimkit Game pada Materi Menganalisis Struktur Teks Negosiasi di Kelas X SMA Negeri 1 Sawo - Telaumbanua, Sararateoli; Ndruru, Mastawati; Waruwu, Lestari; Bu'ulolo, Yanida (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop a Gimkit Game-based learning evaluation tool on the material of analyzing the structure of negotiation text in class X SMA Negeri 1 Sawo. The research used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through validity test, reliability test, practicality questionnaire, and learning outcomes test, while data analysis was done descriptively quantitative to measure the level of validity, reliability, practicality, and effectiveness. The results showed that in the small group trial, 17 multiple choice questions were declared valid, while in the field trial there were 19 valid questions. The reliability value using Cronbach's Alpha reached 1.000 in the small group trial and 0.953 in the field trial. Validation by material and language experts obtained a percentage of eligibility of 96% and 100% respectively. The practicality of the learning evaluation tool reached 97% in the small group trial and 95% in the field trial. Its effectiveness can be seen from the students' learning completeness of 80% in the small group trial and 90% in the field trial. Thus, this Gimkit Game-based learning evaluation tool is proven to be valid, reliable, practical, and effective in the learning process.